Economic Clusters as a Form of Self-Organization of the Economic System - Shiryaev, Dmitry V.; Litvinenko, Inna L.; Rubtsova, Natalya V.; Kolpak, Eugeny P.; Blaginin, Viktor A.; Zakharova, Elena N. (International Journal of Economics and Financial Issues, 2016)
The creation of clusters of domestic innovative economy in the Russian Federation is one of the actual directions of intensification of economic and innovative development of the city, region, and country. The importance of this is proved by the fact that when analyzing the direction of development of the country the Government of the Russian Federation has invited Harvard professor Michael Porter, ancestor of the modern theory of competition (Markov, 2007) one of which main provisions is the need for economy clustering as the only independent expert. Nowadays there is the pressing problem and the need for self-organization of the domestic economic system including its regionalization (Larina & Makeev, 2006). Economic clusters are the most theoretically developed and passed experimental test way of self-organization. Economic clusters as structures of self-organization can occur spontaneously or due to induction. In the first case it is the usual process of the economic basis with corresponding criteria of increasing economic feasibility and, in particular, competitiveness. Participation of the Russian Federation in this case comes down to various ways of assistance. The second one is expressed through a system case of organizational innovation. It can be mostly realized with direct interests and spearheaded by the government. Keywords: cluster, system, economy, self-organization, region JEL Classifications: A10, C38, O10